2002
DOI: 10.1016/s0168-6496(02)00371-9
|View full text |Cite
|
Sign up to set email alerts
|

The transfer dynamics of Pseudomonas sp. plasmid pQBR11 in biofilms

Abstract: Plasmid pQBR11 (294 kb) is one of a group of genetically similar conjugative plasmids that are common to and persist in pseudomonad populations colonising leaves and roots of crops and wild plants. This plasmid was marked by insertion of a green fluorescent protein reporter cassette to facilitate epifluorescence microscopy tracking and enumeration of transconjugant formation in biofilms. The intrinsic transfer activity of the plasmid, the conditions which affect this activity and the patterns of infectious spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The outcome of the EA clearly indicated the importance of nutrients. This correlation between high nutrient levels and elevated transconjugant counts has been demonstrated earlier (Fernandez-Astorga et al, 1992;Lilley & Bailey, 2002;Verma et al, 2002). The increased proportion of transconjugants at high nutrient concentrations can be a result of different factors: (1) the plasmid transfer rate increased; (2) the differences in growth rates of the donors and recipients; and (3) the final growth density of transconjugants and recipients.…”
Section: Ramossupporting
confidence: 58%
“…The outcome of the EA clearly indicated the importance of nutrients. This correlation between high nutrient levels and elevated transconjugant counts has been demonstrated earlier (Fernandez-Astorga et al, 1992;Lilley & Bailey, 2002;Verma et al, 2002). The increased proportion of transconjugants at high nutrient concentrations can be a result of different factors: (1) the plasmid transfer rate increased; (2) the differences in growth rates of the donors and recipients; and (3) the final growth density of transconjugants and recipients.…”
Section: Ramossupporting
confidence: 58%
“…3). Although pQBR55 and pQBR103 had comparatively low rates of conjugation (Simonsen et al, 1990;Gordon, 1992;Lilley and Bailey, 2002), pQBR57 showed an exceptionally high conjugation rate (effect of plasmid F 2,14 = 47.633, P < 0.001) and serial passage of pQBR57 conjugation mixtures in Hg(II)-free KB broth found that 100% of the tested recipient population was Hg R after 10 transfers (480 h). Rates of conjugation were found to be slightly higher for all plasmids in soil compared with KB broth (effect of medium F1,14 = 14.217, P = 0.002), consistent with other findings showing an increased rate of transfer on surfaces (e.g.…”
Section: Rates Of Conjugative Transfer and Segregational Lossmentioning
confidence: 98%
“…Stephens et al . (1987) showed that a naturally occurring lytic phage was responsible for the decline et al., 1988, 1998Lilley et al, 1994Lilley et al, , 2002Björklöf et al, 1995;Hoffmann et al, 1998;Kroer et al, 1998) Transformation (Nielsen & van Elsas, 2001;Kay et al, 2002b) II: Direct, disruptive Extractive, cultivation-based coupled to molecular analysis Plants in field soil MGE transfer in the phytosphere (Lilley et al, 1994;Lilley & Bailey, 1997;van Elsas et al, 1998van Elsas et al, , 2000 III: Retrospective Isolation of MGE, molecular (sequence) analysis Field: soil (aquatic, clinical) Detection of (sequences of) MGE, providing evidence of gene transfer (Hill et al, 1994;Götz et al, 1996;Levin & Bergström, 2000;Ochman et al, 2000;Smalla et al, 2000) IV: Direct, nondisruptive Donor-repressed gfp-labelled MGE Biofilms in laboratory (and nature)…”
Section: Evidence For the Involvement Of Hot Spots In Hgtmentioning
confidence: 99%